Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Nguyễn Phan Anh

cho ab+bc+ac =1 tính P= (a+b+c-abc)^2/(a^2+1)(b^2+1)(c^2+1)

Akai Haruma
4 tháng 2 2024 lúc 23:00

Lời giải:

Với $ab+bc+ac=1$ ta có:

$a^2+1=a^2+ab+bc+ac=(a+b)(a+c)$

$b^2+1=b^2+ab+bc+ac=(b+c)(b+a)$

$c^2+1=c^2+ab+bc+ac=(c+a)(c+b)$

$\Rightarrow (a^2+1)(b^2+1)(c^2+1)=[(a+b)(b+c)(c+a)]^2(*)$

Mặt khác:

$a+b+c-abc=(a+b+c)(ab+bc+ac)-abc$

$=ab(a+b)+bc(b+c)+ca(c+a)+2abc$

$=ab(a+b+c)+bc(b+c)+ca(c+a)$
$=(a+b+c)(ab+bc)+ca(c+a)=b(a+b+c)(c+a)+ca(c+a)$

$=(c+a)[b(a+b+c)+ca]=(c+a)(b+a)(b+c)$

$\Rightarrow (a+b+c-abc)^2=[(a+b)(b+c)(c+a)]^2(**)$

Từ $(*); (**)\Rightarrow P=1$